Influence of organizational structure on risk management of Malaysian construction companies - Omer, Manal Suliman; Adeleke, A. Q. (Inderscience, 2020)
The construction sector plays a significant role in contributing to a country’s economy. But a very important aspect which has been overlooked over the years in project planning is risk assessment. This attitude has been leading to the poor performance and productivity of construction companies. This situation therefore, calls for an empirical search regarding the role that coercive pressure plays in the connection between the structure of an organisation and the management of risk among construction companies in Malaysia. As established in this study’s model, data was gathered from (180) G7 contractors operating in peninsular Malaysia, using a quantitative approach. One hundred and sixty-five (165) copies of the questionnaire were returned and analysed. Smart PLS 3.2.8 was the analytical tool employed for the analysis of the data. The results revealed significant support of all hypotheses. The obtained results showed significant positive relationship between formalization, centralization and construction risk management. Similarly, the results indicated a significant positive relationship between coercive pressure and construction risk management. Furthermore, coercive pressure played a moderating role in the connection between formalization, centralization and management of risk. The study was investigated in peninsular Malaysia. Future study may include other states such as Sabah and Sarawak.